2017
DOI: 10.4103/jos.jos_149_16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different intracoronal bleaching methods on shear bond strength of ceramic brackets bonded to bleached enamel: An in-vitro study

Abstract: OBJECTIVE:To investigate the effect of different intracoronal bleaching methods on the shear bond strength and site of failure of ceramic brackets.MATERIALS AND METHODS:Sixty freshly extracted human maxillary incisors were randomly divided into four groups (n = 15). Endodontic access cavity was prepared and root canals were filled, root fillings were removed 2mm apical to the cementoenamel junction, and a 2-mmthick layer of glass ionomer cement base was applied. Group 1 served as the control. Intracoronal blea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…We observed statistically significant difference on comparing the mean shear bond strength in between various study groups (Table 3). Our results were in correlation with the results obtained by Chauhan et al 15 who also reported similar findings in their study. Oztaş et al 16 assessed the impact of bleaching and late bonding on the shear bond strengths of metal and ceramic brackets bonded with light and chemically cured composite resin to human teeth.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We observed statistically significant difference on comparing the mean shear bond strength in between various study groups (Table 3). Our results were in correlation with the results obtained by Chauhan et al 15 who also reported similar findings in their study. Oztaş et al 16 assessed the impact of bleaching and late bonding on the shear bond strengths of metal and ceramic brackets bonded with light and chemically cured composite resin to human teeth.…”
Section: Discussionsupporting
confidence: 94%
“…From the results, they concluded that shear bond strength is unaffected by 20% CP. Impact of various methods of bleaching on the shear bond strength of ceramic brackets was assessed by Chauhan et al 15 They analyzed 60 freshly extracted maxillary central incisors and randomly divided into four study groups with 15 specimens in each group. They prepared the access cavity in all the extracted teeth, and after completing the root canal process, they removed the filling from cementoenamel junction till 2 mm short of apex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the marginal sealing of temporary restorations can be affected by bleaching reactions [13,21] Loss of marginal integrity opens a microscopic space between the tooth and the restoration, leading to a cascade of events, such as leakage of bleaching components into the oral cavity, causing an acid taste, irritation, localized desquamation of the adjacent gingival and periodontal tissues, leakage of oral fluids and bacteria into the chamber cavity as well as a decrease in the effectiveness of the treatment [21][22][23][24][25][26]. The exact mechanism explaining peroxides action on each tooth substrate bleaching has not yet been fully elucidated [6,18,27,28], but over the years various authors have demonstrated that intracoronal bleaching agents also reach enamel [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of intracoronal bleaching focused on tooth fracture resistance, composition of calcium-silicate cements, their compressive strength, and bond strength to composite resin, adhesive bonding, orthodontic brackets www.srpskiarhiv.rs "Walking bleach" technique bonding to enamel and marginal integrity of temporary and permanent restorative materials following various intracoronal bleaching protocols [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%